2013
DOI: 10.1007/s11548-013-0929-0
|View full text |Cite
|
Sign up to set email alerts
|

Interventional radiology virtual simulator for liver biopsy

Abstract: We present here a new simulator for visceral needle puncture training in interventional radiology. This is the result of a close collaboration between different universities, involving computer scientists, clinicians and clinical engineers. Together, we address the need of segmentation, physically-based modelling, haptics rendering, pseudo-ultrasound generation and the conception of a mannequin required to build an efficient real-time simulator. Clinical face and content validations have also been performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Typical simulators for radiology or surgical simulation have revolved around creating models, either in the virtual world with simulated haptic feedback, manufactured crudely from unrealistic materials or from biological tissues (Vidal et al, ; Petrinec et al, ; Johnson et al, ; Dugo et al, ; Villard et al, ). Only recently have the first examples of 3D‐printed surgical simulators been described.…”
Section: Discussionmentioning
confidence: 99%
“…Typical simulators for radiology or surgical simulation have revolved around creating models, either in the virtual world with simulated haptic feedback, manufactured crudely from unrealistic materials or from biological tissues (Vidal et al, ; Petrinec et al, ; Johnson et al, ; Dugo et al, ; Villard et al, ). Only recently have the first examples of 3D‐printed surgical simulators been described.…”
Section: Discussionmentioning
confidence: 99%
“…There are also many examples of where VR has been used to train the motor skills required to carry out specific medical and surgical procedures (e.g., [6], [10]), including our own work with our collaborators [23], [43] and [30]. Formal validation studies carried out within these projects demonstrated that there is skill transfer from VR to the real world scenario, and that it is possible to discriminate between users with different levels of skill.…”
Section: Training In Vrmentioning
confidence: 99%
“…There are numerous VE systems and applications reported in the literature. Readers who are interested in exploring the broad spectrum of VEs may consult a number of books and literature surveys on the subject [SCS01,Vin13] as well as in specific areas, including, but not limited to, presence [SvKv01,SSU13], haptics [CMJ11], augmented reality [ABB * 01, SFN08], usability evaluation [BGH02], medicine and healthcare [ALF * 11, CJV13,WKL16], flight simulation [Lee05,RS08], education [BFT16], sports [CPW * 12], and cultural and natural heritage [Add00].…”
Section: Related Workmentioning
confidence: 99%